The importance of cross- cultural training in expatriation - Öğütveren, Nida (My University, 2000)
The objective of this research was to define the effects of cross-cultural training on expatriate's success. The sample consisted of 100 subjects, with 50 expatriates who have been in Turkey and their co-workers. A questionnaire was applied to all and an interview was carried out with the expatriates. This research shows that expatriates in Turkey have no training opportunities before overseas assignment. They had never taken any training about cross-cultural Training for whether Turkey nor another assignment. Generally expatriates had an interview with repatriates or people who knows Turkish cultural structure and relationship in daily and business life. This interview helped them at the stage of making decision, about accepting to overseas assignment. According to dialogs made with expatriates by face to face, they sad that training had no effect on adjustment. General opinion is that personal characteristics of expatriate have an important role on the success and adjustment to overseas.
Keywords: İşgücü